The Relationship between Explanatory Ability and Collegiate Learning Assessment Task - Monika Lintang Laksmi; Baskoro Adi Prayitno; Meti Indrowati (Graduate School of Universitas Negeri Malang, 2023)
The literature study discusses the relationship between explanatory ability and Collegiate Learning Assessment (CLA) Task. The method used is a study of the literature related to explanatory ability and CLA Task, the literature studied from 2015 to 2022. The literature study results are CLA Task with an open-ended question, problem-based situations, and problem-solving can be used as an assessment of explanatory abilitys that consist of indicators for justifying procedures, state result, and present explanation. The achievement of the three indicators of explanatory ability that will be empowered with CLA Task needs the help of electronic module for media learning.